Academic Collaboration Challenge Students from Yemeni, Nigeria, and Cambodia at Islamic University in Indonesia - Shihatud D.A. Nabilah; Nasikhin Nasikhin (Jurnal Pendidikan Islam Indonesia, 2024)
Abstract: Academic collaboration is an important element in higher education that supports the exchange of knowledge, skills and experiences between students from various cultural and social backgrounds. In the context of an Islamic University, this study explores the challenges faced by Yemeni, Nigerian, and Cambodian students in academic collaboration. These challenges include cultural and communication differences, as well as their impact on understanding learning methods. The qualitative method of collecting data through resource interviews or field studies is very appropriate for researching this article. The interview was aimed at obtaining two sources' perspectives, namely; international students and teaching staff to collect data. This study aims to identify and analyze the challenges of academic collaboration between students from these three countries, as well as solutions to overcome the obstacles. The results of research examining the challenges of academic collaboration between Yemeni, Nigerian and Cambodian students at Islamic universities, in this article show that there are cultural and linguistic challenges, which have an impact on the understanding of Islamic teachings for Yemeni, Nigerian and Cambodian students in Indonesia. Therefore, there is a need for solutions such as integration between international students and the surrounding environment and provision from the university and from international students themselves before living in Indonesia. In conclusion, this article highlights the challenges and their impacts as well as solutions. Keywords: challenges, collaboration, international students, Islamic university